The Role Of Lecturer Competencıes In Medıateıng Teamwork, Teachıng Experıence, Mastery Of Informatıon Technology On The Performance Of Indonesıan Lecturers - Tri Cicik Wijayanti; Asmirin Noor (Cita Konsultindo Research Center, 2023)
This study aims to examine and analyze the Role of Lecturer Competence in mediating the influence of Teamwork, Teaching Experience, and Mastery of Information Technology on the Performance of Indonesian Lecturers. The data used is primary by using a questionnaire. The population used is lecturers who take part in the Visiting Professor program organized by the University of Muhammadiyah Malang with a total of 362 lecturers. Using a saturated sample, 292 lecturers filled out a questionnaire instrument via Google Form. The analysis technique used Structural Equation Modeling (SEM) with Partial Least Square (PLS) analysis. The results of the study explain that Teamwork is able to have a positive and significant effect on Lecturer Competence, but has an insignificant effect on Lecturer Performance. Teaching Experience has a positive and significant effect on Lecturer Competence and Performance. Mastery of Information Technology has a positive and significant effect on increasing Lecturer Competence, but has no significant effect on Lecturer Performance. Competence is not able to act as a Mediator for the influence of Teamwork on Lecturer Performance, but is able to mediate the effect of Teaching Experience and Mastery of Information Technology on Lecturer Performance